Mesin Pengering Gabah Sistem Refrigerasi - Rusman AR (universitas teuku umar, 2016)
On the drying machine, the refrigeration system works through lowering the temperature of drying air up to the water vapour contained within the air condenses. The drying air should be then reheated till water vapour compression and relative humidity become lower as much as possible. This drying method represents the drying method through constant temperature. Referring to the theoretical analysis that was completely conducted, it was obtained that the drying time could be relatively shorter and faster in comparison with the conventional method for the equal moisture load.